2023
DOI: 10.1055/a-2047-8301
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of P-Chiral, N-Phosphoryl Sulfonamide Brønsted Acids in the Asymmetric Synthesis of 1,2,3,4-Tetrahydroquinoline-2-carboxylate Esters via Biomimetic Transfer Hydrogenation

Abstract: Enantioenriched heterocyclic and rigidified bioisosteres of amino acids are valuable building blocks in drug discovery, particularly in the design of peptidomimetic drugs. The rigidified bioisostere of phenylalanine, 1,2,3,4-tetrahydroquinoline-2-carboxylic acid, is found in a number of biologically active compounds. However, only a small number of successful methodologies have been reported for its asymmetric synthesis. In an effort to develop an environmentally benign and metal-free organocatalytic process f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…In this context, dibenzylaminoesters (60) with electron-deficient aryl groups such as 3,5-(CF 3 ) 2 -C 6 H 3 were found to increase both yield and stereoselectivity. The same is true for diarylphosphine substrates (61) with sterically hindered aryl substituents. The best result for substrates with PO entities [product (S P )-63-O] in terms of enantiomeric excess (90 %) was obtained with mesityl-substituted phosphines (61-Mes) (Table 2, entry 1), as determined by HPLC on a chiral stationary phase.…”
Section: Synthesis By Copper Catalysismentioning
confidence: 70%
See 2 more Smart Citations
“…In this context, dibenzylaminoesters (60) with electron-deficient aryl groups such as 3,5-(CF 3 ) 2 -C 6 H 3 were found to increase both yield and stereoselectivity. The same is true for diarylphosphine substrates (61) with sterically hindered aryl substituents. The best result for substrates with PO entities [product (S P )-63-O] in terms of enantiomeric excess (90 %) was obtained with mesityl-substituted phosphines (61-Mes) (Table 2, entry 1), as determined by HPLC on a chiral stationary phase.…”
Section: Synthesis By Copper Catalysismentioning
confidence: 70%
“…[60] In a subsequent publication, the scope of catalysts and substrates was expanded and it was shown that such catalysts are limited in application at temperatures higher than room temperature, as they tend to racemize upon heating. [61] Nevertheless, this class of organocatalysts Scheme 15. Top: Palladium(II)-catalyzed synthesis of (S P )-93 starting from a P,P-diarylaminophosphine oxide (90) by selective ortho-arylation of one of the Paryl substituents (Ar F = 2,3,5,6-tetrafluorobenzonitrile, BPin = pinacolborane, DMF = dimethylformamide).…”
Section: Applications Of Aminophosphine Oxides As a Novel Class Of Or...mentioning
confidence: 99%
See 1 more Smart Citation